2012
DOI: 10.2174/092986712798992020
|View full text |Cite
|
Sign up to set email alerts
|

Polysaccharide-K (PSK) in Cancer - Old Story, New Possibilities?

Abstract: Polysaccharide-K (PSK, Krestin) is one of the most commonly used medicinal mushroom extracts with a long history as an additive in cancer therapy in Asia, especially in Japan. PSK has a documented anti-tumor activity both in vitro and in vitro, in various types of cancers, including colorectal, gastric, breast, liver, pancreatic, and lung cancer. Despite PSK having been studied for about 40 years as an immune modulator and biological response modifier, the mechanisms of action by PSK have not yet been clearly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…The monosaccharide composition of AIPetinc was determined by Gas Chromatography (GC). For comparison, we also performed parallel experiments on the well-known polysaccharide-protein complex isolated from Trametes versicolor , polysaccharide-K [24]. Table 1 shows that AIPetinc consisted mainly of glucose (88.6%).…”
Section: Resultsmentioning
confidence: 99%
“…The monosaccharide composition of AIPetinc was determined by Gas Chromatography (GC). For comparison, we also performed parallel experiments on the well-known polysaccharide-protein complex isolated from Trametes versicolor , polysaccharide-K [24]. Table 1 shows that AIPetinc consisted mainly of glucose (88.6%).…”
Section: Resultsmentioning
confidence: 99%
“…From the fungi kingdom, polysaccharide-K (PSK, krestin) is one of the most commonly used medicinal mushroom extracts, with a long history in cancer therapy in Asia, especially in Japan [84]. Zhang et al [85] have reported that PSK decreases the invasiveness of a human PC cell line.…”
Section: Phenotypic-target Screening In Pancreatic Cancermentioning
confidence: 99%
“…5A) were round with typical off by inducing their maturation with appropriate "adjuvants". In Asia, PSK is used as an anti-cancer agent for gastric cancer, 9 induction the apoptosis of human leukemia and lymphoma cells, 5 colorectal cancers, 9,10 and small cell lung cancer. 11 PSK has also been reported to resolve the immunosuppressive state of a cancer-bearing host, 12 and might be associated with DC maturation directly.…”
Section: Maturation Of Morphology Phenotype and Functions Of Murine mentioning
confidence: 99%